2017
DOI: 10.3171/2016.9.peds16278
|View full text |Cite
|
Sign up to set email alerts
|

The health belief model and factors associated with adherence to treatment recommendations for positional plagiocephaly

Abstract: OBJECTIVE This study aimed to examine factors associated with adherence to recommended treatment among pediatric patients with positional skull deformity by reviewing a single-institution experience (2007–2014) with the treatment of positional plagiocephaly. METHODS A retrospective chart review was conducted. Risk factors, treatment for positional head shape deformity, and parent-reported adherence were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…11,37 One study by Lam et al analyzed the degree of treatment compliance according to patient subgroups and found that families with public insurance were less likely to adhere to the recommended treatment than families with private insurance (80.2% versus 89.6%). 38 The authors do not discuss the cause, but one possibility is a lack of coverage for required follow-ups. The consensus is that coverage for low-income Americans is insufficient to support multivisit treatment plans, which considerably affects treatment accessibility and can lead to the development of more severe deformities in low-income households.…”
Section: Treatment Burdenmentioning
confidence: 99%
“…11,37 One study by Lam et al analyzed the degree of treatment compliance according to patient subgroups and found that families with public insurance were less likely to adhere to the recommended treatment than families with private insurance (80.2% versus 89.6%). 38 The authors do not discuss the cause, but one possibility is a lack of coverage for required follow-ups. The consensus is that coverage for low-income Americans is insufficient to support multivisit treatment plans, which considerably affects treatment accessibility and can lead to the development of more severe deformities in low-income households.…”
Section: Treatment Burdenmentioning
confidence: 99%
“…The RCF was then applied to the subject of health. Identification of central health risks and aspects are based on reports (e.g., from WHO), health-related theories and models including the Health Belief Model (Hochbaum, 1958;Lam et al, 2017) and health-related beliefs (e.g., Robertson, 2006). Frameworks within risk culture (e.g., Treating Customers Fairly;Financial Services Authority, 2007;and the Culture Framework;McConnell, 2013) and health (the Gateway Model; Kipping et al, 2012) were also considered.…”
Section: Measure Developmentmentioning
confidence: 99%